Interaction of the state and society: updated old agenda - Perepelitsa, Elena V. (Journal of the Belarusian State University. Law, 2022)
The author arises the eternal question of the balance between the state and society. In specifc historical conditions, different models of such tandem are formed. Technological reality makes the inter-subject interaction of the relevant actors complex and contradictory, bringing the social strategies of cooperation and conﬂict to the limit. Initiation to the products of the information age opens up diametrically opposed prospects for the synergistic connection between citizens and government, as well as their alienation. Both scenarios are equally possible for countries with a common Soviet past. The realisation of a favourable scenario and overcoming the crisis of known forms of democracy, which no modern jurisdiction has been able to avoid, depends on many circumstances. Among these are the full-ﬂedged problematisation of this agenda at the level of the national legal doctrine, adequate measures of regulatory policy, the technological independence of the state, the constructive interaction of law with other cognitive experience.
Keywords: communication; digital environment; technological reality; information policy; legitimation; digital platform; network actor